Odpowiedzi

2010-02-05T20:55:16+01:00
A)3x+1 dla x= -1
3*(-1) + 1 = -3+1 = -2

b)5-2y dla y+1
5 - 2*1 = 5 - 2 = 3

c)a(2a+1) dla a+1
1* (2*1+1) = 1* (2+1) = 1*3 = 3

d) s²- 1 dla s+ -3
(-3)² -1 = 9-1 =8
2010-02-05T20:56:40+01:00
A)3x+1=3×(-1)+1=-3+1=-2
b)5-2y=5-2×1=5-2=3
c)a(2a+1)=1×(2×1+1)=1×(2+1)=1×3=3
d)s²-1=(-3)²-1=9-1=8
Najlepsza Odpowiedź!
2010-02-05T20:56:42+01:00
A)3x+1 x=-1
3(-1)+1=-3+1=-2
b)5-2y y=1
5-2(1)=5-2=3
c)a(2a+1) a=1
1(2(1)+1)=1*2+1=3
d)s²- 1 s=-3
(-3)²-1=9-1=8

Proszę o najlepszą ;)